Photochemically Induced Phase Change in Monolayer Molybdenum Disulfide - Byrley, Peter; Liu, Ming; Yan, Ruoxue (Frontiers in Chemistry, 2019)
Monolayer transition metal dichalcogenide (TMDs) are promising candidates for two-dimensional (2D) ultrathin, flexible, low-power and transparent electronics and optoelectronics. However, the performance of TMD-based devices is still limited by the relatively low carrier mobility and the large contact resistance between the semiconducting 2D channel material and the contact metal electrodes. Phase-engineering in monolayer TMDs showed great promise in enabling the fabrication of high-quality hetero-phase structures with controlled carrier mobilities and heterojunction materials with reduced contact resistance. However, to date, general methods to induce phase-change in monolayer TMDs either employs highly-hostile organometallic compounds, or have limited compatibility with large-scale, cost-effective device fabrication. In this paper, we report a new photochemical method to induce semiconductor to metallic phase transition in monolayer MoS2 in a benign chemical environment, through a bench-top, cost-effective solution phase process that is compatible with large-scale device fabrication. It was demonstrated that photoelectrons produced by the band-gap absorption of monolayer MoS2 have enough chemical potential to activate the phase transition in the presence of an electron-donating solvent. This novel photochemical phase-transition mechanism advances our fundamental understanding of the phase transformation in 2D transition metal dichalcogenide (TMDs), and will open new revenues in the fabrication of atomically-thick metal-semiconductor heterostructures for improved carrier mobility and reduced contact resistance in TMD-based electronic and optoelectronic devices.